Nutritional potentials and reproductive effects of Irish potato (Solanum tuberosum) peels on male Wistar rats (2021)
Increasing demand and high cost of conventional animal feed and ingredients have stimulated the search for sustainable alternatives in substances otherwise considered as agricultural or industrial wastes. The present study evaluated the nutritional properties of Irish Potato agro-wastes (peel) (IPP) as an alternative source of feed nutrients, via its effects on haematological, biochemical, antioxidant and reproductive indices using Wistar rats as experimental animal model. Twenty male Wistar rats (100-120 g) were randomly allocated to two dietary treatment groups A and B, with 10 rats in each group. Group A (control) were fed a commercial rat concentrate while Group B rats were fed processed Irish potato peel diet for 2 weeks. The proximate analysis of the diets revealed lower levels of crude protein, energy, fat and ash in IPP, but higher levels of crude fiber, dry matter, moisture and Nitrogen free extract, compared to the control diet. However, IPP recorded lower levels of major anti-nutritional factors (Trypsin Inhibitor, Cyanogenic glycosides, Phytates, Oxalates) compared to the commercial diet. Although IPP led to a significant reduction in the body weights of the rats, there were no changes recorded in most haematological (PCV, Hb, RBC, Platelet count, MCV, MCH and MCHC) and serum chemistry (ALT, AST, ALP) parameters between IPP-fed and control rats. There were observable increases in the activities of antioxidant enzymes (Superoxide dismutase and Glutathione peroxidase) and some markers of oxidative stress (Hydrogen peroxide and Malondialdehyde), as part of a possible adaptive response to IPP. Furthermore, histopathological examination of the liver, kidney and testes did not present any major lesions in both groups of rats, although significant enhancement of sperm motility, livability and sperm count was observed in the IPP-fed rats compared to the control group. This study demonstrates that Irish potato peels possess promising nutritional potentials that should encourage its utilization as an alternative source of animal feed ingredients.